Available transfer capability optimisation using evolutionary programming / Muhammad Murtadha Othman and Bibi Norashiqin Sheikh Rahimullah - Othman, Muhammad Murtadha; Sheikh Rahimullah, Bibi Norashiqin (Institute of Research, Development and Commercialisation (IRDC), 2007)
In a deregulated electric power industry, transmission providers are required to rapidly produce commercially viable information of available transfer capability (ATC) so that such information can help power marketers, sellers and buyers in planning, operation and reserving transmission services. ATC is a measure of the additional amount of power transfer that may flow across the interface, over and above the base case flows without jeopardizing power system security. This paper presents the ATC determination using the evolutionary programming (EP) technique using modified Gaussian formulation. The proposed EP technique has the ability in providing accurate ATC results and the computation burden caused by the AC power flow solutions are significantly reduced. The outages of critical line that adversely affect the amount of ATC are determined by performing the line contingency ranking and selection. ATC determinations have been made on the case study of Malaysian system. Comparison in terms of accuracy and computation time in estimating the ATC are made by considering the three methods which are the EP using modified Gaussian formulation (EPMG), EP using standard Gaussian formulation (EPSG) and the recursive AC power flow solution (RACPF).